2017
DOI: 10.3390/toxins9080241
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Characteristics of Staphylococcus aureus and Staphylococcus argenteus Isolates Harboring Panton-Valentine Leukocidin, Enterotoxins, and TSST-1 Genes from Food Handlers in Myanmar

Abstract: Asymptomatic carriers of toxigenic Staphylococcus aureus are potential source of diseases, including food poisoning. Toxigenic potential and genetic traits of colonizing S. aureus were investigated for 563 healthy food handlers in Myanmar. Carriage of S. aureus was found in 110 individuals (19.5%), and a total of 144 S. aureus isolates were recovered from nasal cavities (110 isolates) and hands (34 isolates). Panton-Valentine leucocidin genes (pvl) were detected in 18 isolates (12.5%), among which 11 isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 57 publications
(97 reference statements)
2
43
0
Order By: Relevance
“…The presence of the PVL gene amongst the S. aureus strains recovered from food samples has been reported previously. 32,33 Recent epidemiological surveys revealed that diseases caused by PVL-positive MRSA strains are more severe with poor prognosis for a longer period of time and mainly do not have satisfactory response to therapeutic agents due to the occurrence of antibiotic resistance. 32,33 PVL-positive MRSA strains were also detected in different types of human clinical infections, particularly wound, burn, pulmonary, urinary tract and gastrointestinal infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of the PVL gene amongst the S. aureus strains recovered from food samples has been reported previously. 32,33 Recent epidemiological surveys revealed that diseases caused by PVL-positive MRSA strains are more severe with poor prognosis for a longer period of time and mainly do not have satisfactory response to therapeutic agents due to the occurrence of antibiotic resistance. 32,33 PVL-positive MRSA strains were also detected in different types of human clinical infections, particularly wound, burn, pulmonary, urinary tract and gastrointestinal infections.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Recent epidemiological surveys revealed that diseases caused by PVL-positive MRSA strains are more severe with poor prognosis for a longer period of time and mainly do not have satisfactory response to therapeutic agents due to the occurrence of antibiotic resistance. 32,33 PVL-positive MRSA strains were also detected in different types of human clinical infections, particularly wound, burn, pulmonary, urinary tract and gastrointestinal infections. 32,33 MRSA strains harbored only SCCmec types IV and V. MRSA is often sub-categorized as healthcare-associated MRSA (HA-MRSA) and community-associated MRSA (CA-MRSA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IT was recently reported in 2020, that Sags particularly the S. aureus enterotoxins play important role in the induction of asthma of hospitalized patients by inducing IgE production [13]. S. aureus strains secrete up to 23 of at least 24 serologically distinct SAgs including TSST-1, SEs and the SE-like (SE-l) [8,14,15]. These SAgs have the distinctive capability to concurrently bind both major histocompatability complex and the T-cell receptor, exerting immune response 20% greater than that of ordinary antigens [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…In our case, no epidemiologic link to Asia or the West Pacific region was observed. The clinical spectrum of infections with S. argenteus remains poorly described, but varies from asymptomatic nasal carriage ( 8 ) to community-acquired infections, including skin and soft tissue infections ( 1 , 6 ), bacteremia ( 1 , 9 ), and foodborne illness ( 8 ). Apart from 2 cases of bacteremia reported by Dupieux et al ( 9 ), clinical data for S. argenteus infections have been poorly detailed ( Technical Appendix Figure).…”
mentioning
confidence: 99%